PENERAPAN PENDEKATAN NARASI UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA PENJUMLAHAN DAN PENGURANGAN PADA KELAS 1SD KRISTEN CITRA BANGSA MANDIRI - Vera Rosalina Bulu; Adam B.N.Benu; Benedikta P.B Koten (STKIP Subang, 2025)
This research is motivated by the low problem-solving skills of Grade 1C studentsat SD Kristen Citra Bangsa Mandiri Kupang. The aim of this study is to improvemathematical problem-solving skills, particularly in the topics of addition andsubtraction in that class.The research employs a Classroom Action Research(CAR) method. Data collection techniques included observations of teacher andstudent activities, as well as written tests. The instruments used were observationsheets and test questions. The subjects of this research were 21 Grade 1Cstudents, consisting of 10 boys and 11 girls. Data analysis was conducted byanalyzing the results of observations and problem-solving tests.The findingsshowed a significant improvement in problem-solving skills. Learning masteryincreased from 47.66% in the pre-cycle to 71.42% in cycle I, and reached 85.71%in cycle II. Improvements were also seen in the observation results of teacher andstudent activities. In cycle I, teacher activity reached 69.11% and 70.58%, whilestudent activity according to observer one was 65% and 68.33%, and according toobserver two was 60% and 71.66%. In cycle II, observer one recorded an increaseto 81.66% and 83.33%, and observer two recorded 85% and 81.66% for teacheractivities, and 81.25% and 84.37% for student activities. Based on these results, itcan be concluded that the use of a narrative approach is effective in improvingstudents’ problem-solving skills in addition and subtraction material.